A new species of Miconia from the remaining primary forest at Las Cruces Biological Station in Costa Rica - Kriebel, Ricardo; Oviedo-Brenes, Federico (Phytotaxa, 2013)
A new species of Miconia, M. povedae is described from a small remnant of primary forest at Las Cruces Biological Station in San Vito, Puntarenas province, Costa Rica. The new species is distinguished by its orangish indument of dendritic and stellate trichomes on most parts of the plant, sessile leaves with a tapering leaf base and strongly plinerved and asymmetric leaf venation, deflexed inflorescences, sessile herkogamous flowers with fused calyces that rupture at anthesis and geniculate staminal filaments. M. povedae is related to a group of for the most part Costa Rican and Panamanian endemics and the distinctive features of M. povedae and these species are discussed. Photographs of live plants, dissections of flowers preserved in ethanol, Scanning Electron Micrographs of leaf trichomes and a distribution map are provided.